A systematic review on intra-arterial cerebral infusions of chemotherapeutics in the treatment of glioblastoma multiforme: The state-of-the-art - Pinkiewicz, Mateusz; Pinkiewicz, Milosz; Walecki, Jerzy; Zawadzki, Michał (Frontiers in Oncology, 2022)
Objective: To provide a comprehensive review of intra-arterial cerebral infusions of chemotherapeutics in glioblastoma multiforme treatment and discuss potential research aims. We describe technical aspects of the intra-arterial delivery, methods of blood-brain barrier disruption, the role of intraoperative imaging and clinical trials involving intra-arterial cerebral infusions of chemotherapeutics in the treatment of glioblastoma multiforme. Method: 159 articles in English were reviewed and used as the foundation for this paper. The Medline/Pubmed, Cochrane databases, Google Scholar, Scielo and PEDro databases have been used to select the most relevant and influential papers on the intra-arterial cerebral infusions of chemotherapeutics in the treatment of glioblastoma multiforme. Additionally, we have included some relevant clinical trials involving intra-arterial delivery of chemotherapeutics to other than GBM brain tumours. Conclusion: Considering that conventional treatments for glioblastoma multiforme fall short of providing a significant therapeutic benefit, with a majority of patients relapsing, the neuro-oncological community has considered intra-arterial administration of chemotherapeutics as an alternative to oral or intravenous administration. Numerous studies have proven the safety of IA delivery of chemotherapy and its ability to ensure higher drug concentrations in targeted areas, simultaneously limiting systemic toxicity. Nonetheless, the scarcity of phase III trials prevents any declaration of a therapeutic benefit. Given that the likelihood of a single therapeutic agent which will be effective for the treatment of glioblastoma multiforme is extremely low, it is paramount to establish an adequate multimodal therapy which will have a synergistic effect on the diverse pathogenesis of GBM. Precise quantitative and spatial monitoring is necessary to guarantee the accurate delivery of the therapeutic to the tumour. New and comprehensive pharmacokinetic models, a more elaborate understanding of glioblastoma biology and the effective methods of diminishing treatment-related neurotoxicity are paramount for intra-arterial cerebral infusion of chemotherapeutics to become a mainstay treatment for glioblastoma multiforme. Additional use of other imaging methods like MRI guidance during the procedure could have an edge over X-ray alone and aid in selecting proper arteries as well as infusion parameters of chemotherapeutics making the procedure safer and more effective.